LITERATURE STUDY: THE USE OF ELECTRONIC CORRESPONDENCE APPLICATION ON WORK EFFECTIVENESS AND TIME EFFICIENCY OF EMPLOYEES IN GOVERNMENT AGENCIES - Deddy Kristanto; Mochammad Subagio (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2024)
In a government system, the existence of government agencies or institutions has main tasks and functions in accordance with their fields of work. In internal relations within an agency and external relations, communication is usually carried out in writing or correspondence. In internal relations, employees carry out tasks according to the disposition of their superiors and tasks in the form of making letters or documents are sent back to their superiors and if needed will be sent to other parties. In external relations, there are many outgoing letters and incoming letters, the number of which can reach hundreds per day so that if the correspondence system is carried out manually, it causes time inefficiency, and work effectiveness in addition to the accumulation of letters so that special management is needed regarding the correspondence system. The existence of a manual correspondence system also causes various impacts such as the length of making letters, letters not received directly, lost letter files and so on. The Central Government has implemented the use of an electronic application called Srikandi in all Government agencies which can not only be used for electronic filing media but also used for correspondence management. This paper is based on a literature study. Researchers are interested in seeing the extent to which the effectiveness of the use of electronic correspondence applications on work effectiveness and employee time efficiency. Keywords: Effectiveness, Correspondence Applications